New avenues in epigenetic research about race: Online activism around reparations for slavery in the United States. (March 2020) - Grossi, Élodie
In recent years, many studies invoking epigenetic mechanisms have focused on nutrition, studying the epigenetic incidence of stress in African-American populations who suffered the trauma of slavery or on prenatal stress transmitted from African-American mothers to their offspring. According to some studies, this traumatic memory is transmitted according to a transgenerational mechanism and induces a modification of the epigenome (which is to be understood as a key variable in the expression of an individual's genes) of a large number of individuals whose ancestors – still according to these studies – underwent a metabolic change related to slavery, due, notably, to nutritional deprivations. While the transgenerational transmission mechanism of trauma is still being questioned by many epigenetic researchers today, and thus not universally accepted by the peer community, it is interesting to consider that activists in favor of reparations related to slavery, especially African Americans, as well as anthropologists and philosophers, are increasingly citing this reasoning of cause and effect as 'proof'– which allegedly demonstrates that 'race' has indeed entered the body through the epigenome. This new research, coupled with its wide reception, have contributed to define biology as an object that is 'social', and which individuals can therefore exploit to their advantage in their demands for reparations. This article will therefore seek to cast light upon the complex intertwinement between the field of epigenetic productions and the circulation of theories and concepts in activists' circles demanding reparations, as well as in newspapers featuring science columns.